Competency-Based Instruction in Communicative Language Teaching - qizi, Suyunova Mohinur Ilhom (European Journal of Life Safety and Stability (2660-9630), 2022)
Competency-based language teaching (CBLT) is an application of the principles of competency-based education. It concerns accountability, management and quantification. CBLT focuses on the competencies and outputs. If teaching competencies becomes an end in itself, stakeholders become the object rather than the subjects of the educational process. On the other hand, if competencies are seen as tools to enable learners to act for change in their lives, critical thinking will be promoted. After a brief history, this article introduces competency-based language teaching. Then it will be followed by how it will be evaluated. Finally the pros and cons of this kind of instruction are elaborated in details.